Applications of evacuated tubes collector to harness the solar energy: a review. Issue 1 (31st December 2022) - Mevada, Dinesh; Panchal, Hitesh; ElDinBastawissi, Hagar Alm; Elkelawy, Medhat; Sadashivuni, Kishorkumar; Ponnamma, Deepalekshmi; Thakar, Nishant; Sharshir, S. W.
Abstract : Solar energy is a need of an hour. At present, due to the global warming effect, researchers are moving towards the research work on solar energy. Solar energy can be harnessed by solar thermal collectors. Flat plate collector, evacuated tubes collector, parabolic concentrator, etc. are used as efficient apparatus to use thermal energy for useful application. Among the above collectors, evacuated tubes collector is famous as compared with others due to the lower heat loss. This review paper shows various applications of evacuated tubes collector like solar water heating, solar drying, solar air heating, and solar desalination. It has been found that evacuated tubes collector is the most suitable apparatus for solar thermal applications.